Creating the conscious law firm: What traditional law firms can learn from the conscious capitalism movement (Part 3) - Duperouzel, Christian (Law Council of Australia, 2020)
In the third and final part of a series, Dr Christian Duperouzel explains how law firms can develop a structure for creating a conscious law firm that enriches stakeholders and puts the focus on serving a higher purpose rather than simply making profits.